(untitled) (Agricultural Engineering, 2020)
In the aspect of the course and analysis of products of biomass fuels combustion in grill feed boilers, the combustion process of wheat straw and meadow hay were assessed taking into consideration conditions of SO2 emission. Different types of briquettes used in the research not only had various chemical properties but also physical properties. In the aspect of assessment of energy and organic parameters of the combustion process, the sulphur content in biomass becomes a significant factor at its energy use. Registered emission during combustion of meadow hay biomass referred to wheat biomass was for A and B type briquettes correspondingly higher by ca. 320 and 120%. Differences in SO2 emission at combustion of various biofuel forms in the aspect of the relation with the remaining combustion parameters including mainly with air flow require, however, further research that leads to development of low-emission and high-efficient biofuel combustion technologies in low-power heating devices.